2018
DOI: 10.1111/ilr.12121
|View full text |Cite
|
Sign up to set email alerts
|

Gendered costs of austerity: The effects of welfare regime and government policies on employment across the OECD, 2000–13

Abstract: This article proposes a thorough analysis of the gendered impact of government policies applied during the Great Recession on unemployment across 28 OECD countries following an empirical estimation using random effects modelling with data from 2000 to 2013 to test the influence of welfare systems. Results point to a significant effect of welfare regime even beyond the crisis, primarily through social expenditure levels and public sector employment dynamics, which mainly affect women. The detailed policy analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Because of historical and current employment practices, where women and minorities face disadvantages in recruitment processes (Padavic, Reskin et al 2002) and retention practices (Diebold, Neumark, and Polsky 1997;Hall, Gordon, and Holt 1972;Ureta 1992) in the USA, Canada, and other similar developed countries, these employment adjustments disproportionately affect women (Diebold, Neumark, and Polsky 1997;Hall, Gordon, and Holt 1972;Sheeran 1975;Ureta 1992). Recent studies (Kushi and McManus 2018;Women's Budget Group 2018) have shown that in countries with greater gender discrimination, women are more likely than men to be exposed to the downside risks associated with trade liberalization and other economic shocks.…”
mentioning
confidence: 99%
“…Because of historical and current employment practices, where women and minorities face disadvantages in recruitment processes (Padavic, Reskin et al 2002) and retention practices (Diebold, Neumark, and Polsky 1997;Hall, Gordon, and Holt 1972;Ureta 1992) in the USA, Canada, and other similar developed countries, these employment adjustments disproportionately affect women (Diebold, Neumark, and Polsky 1997;Hall, Gordon, and Holt 1972;Sheeran 1975;Ureta 1992). Recent studies (Kushi and McManus 2018;Women's Budget Group 2018) have shown that in countries with greater gender discrimination, women are more likely than men to be exposed to the downside risks associated with trade liberalization and other economic shocks.…”
mentioning
confidence: 99%
“…Thus, the decision to engage in formal employment also depends on the normative context in which the decision-making is embedded. This means that those women who are expected to shoulder a larger share of house work and family support see their capacity for formal employment undermined (Kushi and McManus 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, these measures appear to be having a differential effect, since the worst affected, alongside the older and low-income groups, are women, who are often more dependent on state income support and social services than men (Karamessini and Rubery 2014b) and thus more vulnerable to austerity measures (Rubery 2015;Kushi and McManus 2018). The deterioration of the welfare state, 2…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a detailed discussion of the gendered effects of welfare regime on employment, seeKushi and McManus (2018), in this issue of the International Labour Review, pp. 557-587.…”
mentioning
confidence: 99%